The efficacy and safety of tislelizumab in the treatment of locally advanced or metastatic lung cancer: a systematic review and meta-analysis - Zhou, Yue; Liu, Sanmao; Zheng, Shaochu; Han, Jiahui; Huang, Haizhu; Kong, Jinliang (Frontiers in Pharmacology, 2025)
ObjectiveThe clinical role of Tislelizumab in patients with locally advanced or metastatic lung cancer (LC) remains controversial. This study aims to systematically evaluate the efficacy and safety of Tislelizumab in treating these patients through a meta-analysis.MethodsDatabases including PubMed, Cochrane Library, Embase, and Web of Science were searched up to 19 May 2025. Randomized controlled trials (RCTs) and single-arm studies assessing the efficacy and safety of Tislelizumab for locally advanced or metastatic LC were included. Literature screening and data extraction were performed according to the PRISMA guidelines, and pooled odds ratios (OR) and their 95% confidence intervals (CI) were calculated using STATA 15.0 software.ResultsA total of 8 studies were included, of which 5 were RCTs and 3 were single-arm studies. In the RCT subgroup, the Tislelizumab group demonstrated a higher objective response rate (ORR) [OR = 2.29, 95%CI(1.43,3.64), P = 0.001] and disease control rate (DCR) [OR = 1.64, 95%CI(1.30,2.07), P < 0.001] compared to the control group, but no significant differences were found in overall survival (OS) [OR = 0.81, 95%CI(0.60,1.10), P = 0.179] or progression-free survival (PFS) [OR = 0.74, 95%CI(0.39,1.41), P = 0.364]. Single-arm study data indicated that Tislelizumab treatment achieved a high ORR [OR = 0.54, 95%CI (0.34,0.74), P < 0.001] and DCR [OR = 0.86, 95%CI (0.78,0.92), P < 0.001]. Subgroup analysis revealed that Tislelizumab had similar effects on ORR and DCR in non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC).ConclusionThe meta-analysis results suggest that Tislelizumab demonstrates significant short-term efficacy (ORR and DCR) in patients with locally advanced or metastatic LC. However, the existing evidence is inadequate to confirm its long-term survival benefits (OS and PFS), and more high-quality studies are needed for validation.